Nanometer coating for decomposing dirt on photovoltaic panel based on photocatalysis technology
By applying nanocoating based on photocatalytic technology on photovoltaic panels, the problem of high cost and possible damage to photovoltaic panels in traditional cleaning methods is solved, efficient self-cleaning effect is achieved, operation and maintenance costs are reduced, and photovoltaic power generation is significantly improved Efficiency and service life.
Patent Information
- Application Number
- CN202411829941.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional PV panel cleaning measures are costly and improperly operated may damage the surface of the PV panel, resulting in reduced power generation efficiency and shortened service life.
Nanocoating based on photocatalytic technology is adopted, including the base nanosilver and a self-cleaning layer, which contains titanium dioxide, zinc oxide, iron oxide and zirconium dioxide nanoparticles. By constructing a concave and convex structure below 50 nm, the self-cleaning effect is achieved.
Effectively reduces the cleaning frequency of more than 80%, reduces manual operation and maintenance, reduces operation and maintenance costs, improves photovoltaic power generation efficiency, extends the service life of photovoltaic panels, and has a sustained age range of 5 years in different regions. , non-northwest region for 5-8 years.
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano coatings, in particular to a nano coating for decomposing photovoltaic panel dirt based on photocatalytic technology. Background Art
[0002] Photovoltaic panels, also known as solar panels, are devices that can convert solar energy into electrical energy. They are generally found on large-scale solar power plant sites. Many households choose to install photovoltaic panels on their roofs or exterior walls. The application of photovoltaic panels in the transportation field is also gradually increasing, providing electricity for these vehicles through solar energy.
[0003] Photovoltaic modules are exposed to wind and sun all year round. Due to on-site environmental factors, the surface of photovoltaic glass modules is polluted and dust accumulates, which reduces the life and power generation efficiency of photovoltaic modules. Pollution adheres to the photovoltaic glass, causing the light transmittance to decrease. Over time, hot spots will form on the surface of the photovoltaic glass, turning it from generating electricity to consuming electricity. In order to reduce the impact of the environment on the power generation of photovoltaic equipment, power stations usually arrange personnel to clean photovoltaic modules on a regular basis. However, the existing manual cleaning method not only causes huge cleaning costs, but also improper construction will damage the original surface coating of the photovoltaic panels and accelerate the attenuation. Therefore, it is urgent to introduce green, environmentally friendly, economical and efficient photovoltaic module performance maintenance methods to extend their service life, improve photovoltaic power generation efficiency, and increase the use benefits.
[0004] Therefore, in view of the high cleaning cost of the above-mentioned traditional photovoltaic panel cleaning measures and the damage to the surface of the photovoltaic panels caused by improper operation during the cleaning process, a nano-coating based on photocatalytic technology can be designed to decompose the dirt on the photovoltaic panels. Summary of the invention
[0005] In order to overcome the high cleaning cost of traditional photovoltaic panel cleaning measures, improper operation during the cleaning process may also cause damage to the surface of the photovoltaic panel.
[0006] The technical solution of the present invention is: a nano coating for decomposing dirt on photovoltaic panels based on photocatalytic technology, with nano silver used as the bottom layer;
[0007] The self-cleaning layer is formulated as follows by weight: 60 to 70 parts of titanium dioxide nanoparticles, 10 to 20 parts of zinc oxide nanoparticles, 5 to 10 parts of iron oxide nanoparticles, 5 to 10 parts of zirconium dioxide nanoparticles, 60 to 120 parts of solvent, 1 to 3 parts of dispersant, 0.5 to 1.5 parts of thickener, and 1 to 3 parts of rust inhibitor;
[0008] The steps for preparing the photovoltaic panel nano coating are as follows:
[0009] Step 1, preparation of nanoparticles: titanium dioxide, zinc oxide, iron oxide, and zirconium dioxide materials are measured according to weight, and the above materials are prepared into nanoparticle states respectively;
[0010] Step 2: Preparation of nano coating solution:
[0011] Preparation of bottom solvent, dispersing nano silver material in solvent, and preparing nano coating solution A by ultrasonic dispersion;
[0012] Preparation of self-cleaning layer solvent: dispersing titanium dioxide nanoparticles, zinc oxide nanoparticles, iron oxide nanoparticles, and zirconium dioxide nanoparticles in a solvent, adding a dispersant, a thickener, and a rust inhibitor, and preparing a nano coating solution B by high-speed stirring;
[0013] Step 3: Surface treatment: Use detergent and water to remove dust and dirt from the surface of the photovoltaic panel to ensure that the surface is clean and free of impurities, and then use a polishing machine to trim the surface of the photovoltaic panel;
[0014] Step 4: Coating process:
[0015] For bottom layer processing, pour an appropriate amount of nano coating solution A into a container, immerse the photovoltaic panel with the surface facing downward into the coating for 3 to 5 seconds. The thickness of the bottom layer shall not exceed 15nm. Then take out the photovoltaic panel coated with the bottom layer for drying and curing.
[0016] For self-cleaning layer processing, pour an appropriate amount of nano-coating solution B into the ultrasonic spraying equipment, spray the nano-coating solution B evenly on the surface of the photovoltaic panel, construct a concave-convex structure with a nano-coating thickness of no more than 50nm on the surface of the photovoltaic panel, and then take out the processed self-cleaning layer photovoltaic panel to dry and solidify.
[0017] Preferably, titanium dioxide nanoparticles are prepared by a hydrothermal method, wherein a solution containing a titanium source is slowly poured into a reactor, the reactor is raised to a reaction temperature of 100°C to 250°C, and the solvent is allowed to expand to produce a high-pressure condition of 1MPa to 10MPa. Under high temperature and high pressure, the titanium source undergoes hydrolysis and condensation reactions to form titanium dioxide nanoparticles.
[0018] The hydrothermal method is used to prepare zirconium dioxide nanoparticles. A solution containing a zirconium source is poured into a reactor, and the reactor is heated to a reaction temperature of 100°C to 250°C. The solvent is allowed to expand to produce a high-pressure condition of 1MPa to 10MPa. Under high temperature and high pressure, the zirconium source undergoes hydrolysis and condensation reactions to form zirconium dioxide nanoparticles.
[0019] The sol-gel method is used to prepare iron oxide nanoparticles. Ferric nitrate is dissolved in water and slowly stirred with a stirring rod to form a uniform solution. An appropriate amount of adjusting solution is added to control the pH value of the solution at 2 to 5. Ionic hydrolysis and polymerization are carried out at 60°C to 75°C for 8 to 10 hours to form a sol. The sol is evaporated and gradually converted into a gel. The gel is calcined at a high temperature of 300°C to 800°C to finally remove organic residues to obtain iron oxide nanoparticles.
[0020] The adjusting solution is one of an inorganic acid and an inorganic base.
[0021] The sol-gel method is used to prepare zinc oxide nanoparticles. Zinc salt and deionized water are stirred evenly to form a solution, and the solution is slowly dripped into an ammonia solution. As the zinc ions are hydrolyzed and precipitated, the stirring rod is slowly stirred, and the solution is heated to gradually form zinc hydroxide colloidal particles at 50°C to 60°C. The formed sol is aged into a gel, and the gel is calcined at a high temperature of 300°C to 800°C. Finally, the organic residues are removed to obtain zinc oxide nanoparticles.
[0022] Preferably, in the preparation process of nanoparticles of titanium dioxide, zinc oxide, iron oxide and zirconium dioxide materials in step 1, they need to be ground in advance using a ball mill, and the average particle size of the nanoparticles does not exceed 50 nanometers.
[0023] Preferably, in step 2, the dispersant can be one of polyethylene glycol and polyacrylic acid compounds; the thickener can be one of hydroxyethyl cellulose and methyl cellulose; and the rust inhibitor can be one of organic phosphate and molybdate.
[0024] Preferably, in step three, the photovoltaic panels need to be degreased using an alkaline degreasing agent before the photovoltaic panels are operated on the surface.
[0025] Preferably, the operating frequency of the ultrasonic spraying equipment for processing the self-cleaning layer in step 4 is 20kHz to 40kHz; the spraying pressure is 0.2MPa to 0.5MPa; the curing and drying temperature in step 4 is 60°C to 120°C; and the curing time is 1 hour to 3 hours.
[0026] Beneficial effects of the present invention:
[0027] The present invention abandons the traditional external cleaning method and innovatively adds a bottom layer and a self-cleaning layer on the outside of the photovoltaic panel. The bottom layer as the basis has good conductivity, antibacterial and corrosion resistance, and the self-cleaning layer contains a photocatalyst nano-coating of titanium dioxide nanoparticles, zinc oxide nanoparticles, iron oxide nanoparticles, and zirconium dioxide nanoparticles. The self-cleaning layer of the invention can effectively maintain the transparency of the photovoltaic glass and the photovoltaic power generation efficiency by constructing a concave-convex structure roughness of less than 50nm on the surface of the photovoltaic panel, thereby increasing the photovoltaic power generation. In addition, the nano-coating can induce an oxidation-reduction reaction under light conditions, effectively decompose organic dirt on the surface of the photovoltaic panel, such as bird droppings, leaf residues, etc., reduce the cleaning frequency by more than 80%, reduce the amount of manual operation and maintenance, and significantly reduce the operation and maintenance costs, so as to achieve real cost reduction and efficiency improvement. Compared with conventional cleaning, the initial comprehensive increase in power generation can reach 2.6%, and the long-term increase in power generation is greater than 5%. The coating can last for 5 years in the northwest region and 5-8 years in non-northwest regions. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the embodiments.
[0029] Example 1
[0030] In this specific embodiment, the coating application time is from May 23, 2023 to May 25, 2023, with a construction period of 3 days. The nano-coating for decomposing photovoltaic panel dirt based on the photocatalytic technology of the present invention was successfully put into operation on the rooftop photovoltaic panels in rural Anhui.
[0031] The present invention provides an embodiment: a nano coating for decomposing dirt on photovoltaic panels based on photocatalytic technology, which is composed of a bottom layer and a self-cleaning layer; the bottom layer: nanosilver; the self-cleaning layer comprises 65 parts of titanium dioxide nanoparticles, 10 parts of zinc oxide nanoparticles, 7 parts of iron oxide nanoparticles, 6 parts of zirconium dioxide nanoparticles, 100 parts of solvent, 1 part of dispersant, 0.6 parts of thickener, and 2.5 parts of rust inhibitor;
[0032] The steps for preparing the photovoltaic panel nano coating are as follows:
[0033] Step 1, preparation of nanoparticles: titanium dioxide, zinc oxide, iron oxide, and zirconium dioxide materials are measured according to weight, and the above materials are prepared into nanoparticle states respectively;
[0034] Step 2: Preparation of nano coating solution:
[0035] Preparation of bottom solvent, dispersing nano silver material in solvent, and preparing nano coating solution A by ultrasonic dispersion;
[0036] Preparation of self-cleaning layer solvent: dispersing titanium dioxide nanoparticles, zinc oxide nanoparticles, iron oxide nanoparticles, and zirconium dioxide nanoparticles in a solvent, adding a dispersant, a thickener, and a rust inhibitor, and preparing a nano coating solution B by high-speed stirring;
[0037] Step 3: Surface treatment: Use detergent and water to remove dust and dirt from the surface of the photovoltaic panel to ensure that the surface is clean and free of impurities, and then use a polishing machine to trim the surface of the photovoltaic panel;
[0038] Step 4: Coating process:
[0039] For bottom layer processing, pour an appropriate amount of nano coating solution A into a container, immerse the photovoltaic panel with the surface facing downward into the coating for 3 to 5 seconds. The thickness of the bottom layer shall not exceed 15nm. Then take out the photovoltaic panel coated with the bottom layer for drying and curing.
[0040] For self-cleaning layer processing, pour an appropriate amount of nano-coating solution B into the ultrasonic spraying equipment, spray the nano-coating solution B evenly on the surface of the photovoltaic panel, construct a concave-convex structure with a nano-coating thickness of no more than 50nm on the surface of the photovoltaic panel, and then take out the processed self-cleaning layer photovoltaic panel to dry and solidify.
[0041] Through Example 1, a photovoltaic panel with a nano-coating for decomposing dirt on photovoltaic panels based on photocatalytic technology is provided. When preparing the coating slurry, a larger amount of solvent is used, a smaller amount of dispersant is used, an appropriate amount of thickener and a larger amount of rust inhibitor are added, so that the coating has strong fluidity and is easier to apply, reducing the construction time. At the same time, the nano molecules are evenly distributed, and it has excellent rust prevention performance in areas with more rain in Anhui. After being coated, the photovoltaic panel has excellent conductivity, antibacterial and corrosion resistance. At the same time, the self-cleaning layer can effectively decompose dust and rainwater on the surface of the photovoltaic panel under light conditions, maintaining the transparency and power generation efficiency of the photovoltaic glass.
[0042] Example 2
[0043] The coating time of this specific embodiment is from November 3, 2024 to November 10, 2024, with a construction period of 8 days. The nano-coating for decomposing photovoltaic panel dirt based on photocatalytic technology of the present invention has been successfully put into operation on a large number of photovoltaic panels laid on the ground in Gansu.
[0044] The present invention provides an embodiment: a nano coating for decomposing dirt on photovoltaic panels based on photocatalytic technology, which is composed of a bottom layer and a self-cleaning layer; the bottom layer: nanosilver; the self-cleaning layer comprises 70 parts of titanium dioxide nanoparticles, 10 parts of zinc oxide nanoparticles, 8 parts of iron oxide nanoparticles, 7 parts of zirconium dioxide nanoparticles, 80 parts of solvent, 3 parts of dispersant, 1.5 parts of thickener, and 1.5 parts of rust inhibitor;
[0045] The steps for preparing the photovoltaic panel nano coating are as follows:
[0046] Step 1, preparation of nanoparticles: titanium dioxide, zinc oxide, iron oxide, and zirconium dioxide materials are measured according to weight, and the above materials are prepared into nanoparticle states respectively;
[0047] Step 2: Preparation of nano coating solution:
[0048] Preparation of bottom solvent, dispersing nano silver material in solvent, and preparing nano coating solution A by ultrasonic dispersion;
[0049] Preparation of self-cleaning layer solvent: dispersing titanium dioxide nanoparticles, zinc oxide nanoparticles, iron oxide nanoparticles, and zirconium dioxide nanoparticles in a solvent, adding a dispersant, a thickener, and a rust inhibitor, and preparing a nano coating solution B by high-speed stirring;
[0050] Step 3: Surface treatment: Use detergent and water to remove dust and dirt from the surface of the photovoltaic panel to ensure that the surface is clean and free of impurities, and then use a polishing machine to trim the surface of the photovoltaic panel;
[0051] Step 4: Coating process:
[0052] For bottom layer processing, pour an appropriate amount of nano coating solution A into a container, immerse the photovoltaic panel with the surface facing downward into the coating for 3 to 5 seconds. The thickness of the bottom layer shall not exceed 15nm. Then take out the photovoltaic panel coated with the bottom layer for drying and curing.
[0053] For self-cleaning layer processing, pour an appropriate amount of nano-coating solution B into the ultrasonic spraying equipment, spray the nano-coating solution B evenly on the surface of the photovoltaic panel, construct a concave-convex structure with a nano-coating thickness of no more than 50nm on the surface of the photovoltaic panel, and then take out the processed self-cleaning layer photovoltaic panel to dry and solidify.
[0054] Example 2 provides a photovoltaic panel with a nano-coating based on photocatalytic technology to decompose photovoltaic panel dirt. Compared with Example 1, the coating slurry uses a smaller amount of solvent during preparation, increases the amount of dispersant, and uses more thickener and a smaller amount of rust inhibitor, so that the slurry has sufficient viscosity, is easy to coat, has a high coating success rate, and has strong wear resistance. The coating can last up to 5 years in the northwest region. In the face of sand, gravel, bird droppings, and tree leaves and branches that are commonly seen on the ground in Gansu, the coating can effectively decompose the above-mentioned organic dirt on the surface of the photovoltaic panel after being coated.
Claims
1. Nano-coating for decomposing photovoltaic panel dirt based on photocatalytic technology, characterized in that: It is composed of a bottom layer and a self-cleaning layer; The bottom layer uses nanosilver; The self-cleaning layer is formulated as follows by weight: 60 to 70 parts of titanium dioxide nanoparticles, 10 to 20 parts of zinc oxide nanoparticles, 5 to 10 parts of iron oxide nanoparticles, 5 to 10 parts of zirconium dioxide nanoparticles, 60 to 120 parts of solvent, 1 to 3 parts of dispersant, 0.5 to 1.5 parts of thickener, and 1 to 3 parts of rust inhibitor; The steps for preparing the photovoltaic panel nano coating are as follows: Step 1, preparation of nanoparticles: titanium dioxide, zinc oxide, iron oxide, and zirconium dioxide materials are measured according to weight, and the above materials are prepared into nanoparticle states respectively; Step 2: Preparation of nano coating solution: Preparation of bottom solvent, dispersing nano silver material in solvent, and preparing nano coating solution A by ultrasonic dispersion; Preparation of self-cleaning layer solvent: dispersing titanium dioxide nanoparticles, zinc oxide nanoparticles, iron oxide nanoparticles, and zirconium dioxide nanoparticles in a solvent, adding a dispersant, a thickener, and a rust inhibitor, and preparing a nano coating solution B by high-speed stirring; Step 3: Surface treatment: Use detergent and water to remove dust and dirt from the surface of the photovoltaic panel to ensure that the surface is clean and free of impurities. Then use a polishing machine to trim the surface of the photovoltaic panel. Step 4: Coating process: For bottom layer processing, pour an appropriate amount of nano coating solution A into a container, immerse the photovoltaic panel with the surface facing downward into the coating for 3 to 5 seconds. The thickness of the bottom layer shall not exceed 15nm. Then take out the photovoltaic panel coated with the bottom layer for drying and curing. For self-cleaning layer processing, pour an appropriate amount of nano-coating solution B into the ultrasonic spraying equipment, spray the nano-coating solution B evenly on the surface of the photovoltaic panel, construct a concave-convex structure with a nano-coating thickness of no more than 50nm on the surface of the photovoltaic panel, and then take out the processed self-cleaning layer photovoltaic panel to dry and solidify.
2. The nano coating for decomposing photovoltaic panel dirt based on photocatalytic technology according to claim 1, characterized in that: In step 1, the nanoparticle preparation process of titanium dioxide, zinc oxide, iron oxide, and zirconium dioxide materials needs to be ground in advance using a ball mill, and the average particle size of the nanoparticles does not exceed 50 nanometers.
3. The nano coating for decomposing photovoltaic panel dirt based on photocatalytic technology according to claim 1, characterized in that: In step 2, the dispersant can be one of polyethylene glycol and polyacrylic acid compounds; the thickener can be one of hydroxyethyl cellulose and methyl cellulose; and the rust inhibitor can be one of organic phosphate and molybdate.
4. The nano coating for decomposing photovoltaic panel dirt based on photocatalytic technology according to claim 1, characterized in that: In step three, the photovoltaic panels need to be degreased using an alkaline degreasing agent before surface treatment.
5. The nano coating for decomposing photovoltaic panel dirt based on photocatalytic technology according to claim 1, characterized in that: The working frequency of the ultrasonic spraying equipment for processing the self-cleaning layer in step 4 is 20kHz to 40kHz; the spraying pressure is 0.2MPa to 0.5MPa; the curing and drying temperature in step 4 is 60℃ to 120℃; and the curing time is 1 hour to 3 hours.
Citation Information
Cited By
Self-assembled gradient multifunctional photovoltaic glass coating and preparation method thereof
CN121975436A